2015
DOI: 10.1186/s12931-014-0139-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mRNA expression profiling in vastus lateralis of COPD patients with low and normal fat free mass index and healthy controls

Abstract: BackgroundChronic Obstructive Pulmonary Disease (COPD) has significant systemic effects beyond the lungs amongst which muscle wasting is a prominent contributor to exercise limitation and an independent predictor of morbidity and mortality. The molecular mechanisms leading to skeletal muscle dysfunction/wasting are not fully understood and are likely to be multi-factorial. The need to develop therapeutic strategies aimed at improving skeletal muscle dysfunction/wasting requires a better understanding of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 103 publications
(121 reference statements)
4
83
0
1
Order By: Relevance
“…Using 30mg pioglitazone for 2 weeks increased to 45mg for 10 weeks there were no significant differences in the airway hyper-responsiveness to methacholine, FeNO or lung function between treatment and placebo. Recruitment was halted early (as in our study) due to the impact of emerging safety concerns surrounding the potential risk of bladder cancer affecting recruitment, lack of efficacy signal and significant weight gain in pioglitazone treated patients [19]. The thiazolidinediones are associated with significant adverse effects when administered systemically and these studies support our conclusion that systemic treatment with pioglitazone is not associated with beneficial effects on asthma control.…”
Section: Discussionsupporting
confidence: 66%
“…Using 30mg pioglitazone for 2 weeks increased to 45mg for 10 weeks there were no significant differences in the airway hyper-responsiveness to methacholine, FeNO or lung function between treatment and placebo. Recruitment was halted early (as in our study) due to the impact of emerging safety concerns surrounding the potential risk of bladder cancer affecting recruitment, lack of efficacy signal and significant weight gain in pioglitazone treated patients [19]. The thiazolidinediones are associated with significant adverse effects when administered systemically and these studies support our conclusion that systemic treatment with pioglitazone is not associated with beneficial effects on asthma control.…”
Section: Discussionsupporting
confidence: 66%
“…A systematic review found that postnatal maternal smoking was strongly associated with bronchiolitis (OR 2.51, 95% CI 1.58–3.97) [36]. More recently, prenatal ETS exposure and heavy postnatal maternal smoking were both associated with an increased risk of hospitalization for bronchiolitis in the first year of life; however, postnatal exposure increased the risk by twofold compared to prenatal ETS exposure [44]. Further, both prenatal and postnatal maternal smoking were associated with an increased risk for admission to ICU: OR = 1.51 (95% CI 1.14–2.00) for prenatal and OR = 1.95 (95% CI 1.13–3.37) for postnatal exposure [45].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, NAGS showed no significant difference between the two groups, indicating that body weight was an essential factor affecting muscle function [34]. Muscle mass may play a key role: the studies [35][36][37] available in the literature prove that protein synthesis of myocyte is weakened and the muscle growth is inhibited in COPD, which means that the modeling process may inhibit muscle growth and then inhibit muscle function. Although these hypotheses are not reflected in our results, it suggests that CSE may cause skeletal muscle dysfunction by inhibiting muscle growth, taking into account the importance of muscle mass in body weight.…”
Section: Effect Of Smoke Exposure On the Skeletal Muscles Of Ratsmentioning
confidence: 99%